Improving Breast Cancer Outcomes among Women in China: Practices, Knowledge, and Attitudes Related to Breast Cancer Screening - Tsu-Yin Wu; Yi-Lan Liu; Scott Chung (International Journal of Breast Cancer)
Background. Breast cancer is a major public health issue and the most commonly diagnosed cancer for women worldwide. Despite lower incidence rates than those living in Western countries, breast cancer incidence among Chinese women has increased dramatically in the past 20 years. Nevertheless, there is a paucity of studies reporting the attitudes toward and practices of breast cancer screening among Chinese women. Methods. This cross-sectional study examined the practices, knowledge, and attitudes toward breast cancer screening (BCS) on a convenience sample of 400 Chinese women. Results. Among study participants, 75% of the women never had a mammogram and the top three barriers reported were low priority, feeling OK, and lack of awareness/knowledge toward breast cancer screening. The results from the logistic regression model showed increased self-efficacy; having performed monthly self-exams, and having had clinical breast exams in the past two years were significant correlates while demographic variables were not correlated with screening behaviors. Conclusion. The findings provide a foundation to better understand beliefs and practices of Chinese women toward BCS and highlight the critical need for general public, health professionals, and the health care system to work collaboratively toward improving the quality of breast cancer care in this population.